Design and optimization of mems accelerometer sensor for lower limb exoskeleton application / Muhammad Fareq Ibrahim - Muhammad Fareq , Ibrahim (2018)
Currently a lot of studies have added their focuses into several backgrounds that are known as multi-discipline studies. One of the study is on lower limb exoskeleton which are the combination of electrical, mechanical and biomedical field. Lower limb exoskeleton study evolve on potential of helping disable people to walk again. Lower limb exoskeleton consists of multi components and one of it is the MEMS accelerometer. MEMS accelerometer are used to give an accurate angle at the joint of lower limb exoskeleton because the exoskeleton must be designed to be as similar as possible with the real human’s leg. For this reason, an existing study on design of dual-axis MEMS accelerometer have been selected and simulated by using COMSOL Multiphysics. This design will be studied to obtain the optimal results on maximum stress and displacement sensitivity on X-axis and Y-axis. Three parameters have been modified into ±5%, ±10%, ±15%, ±20%, and ±25% to see their effect which are the lengths and widths of the beam and thickness of device. Taguchi method has been used for the optimization to get the optimal results. From the simulation results and analysis, this study was able to get 26.6419% and 60% of improvement of maximum stress and displacement sensitivity on X-axis and 31.8163% and 61.1556% of improvement of maximum stress and displacement sensitivity on Y-axis.